Endocrine Aspects of Exocrine Cancer of the Pancreas: Their Patterns and Suggested Biologic Significance. Issue 3 (21st January 2016) - Pour, Parviz M.; Permert, Johan; Mogaki, Masashito; Fujii, Hideki; Kazakoff, Katherine
Abstract : Nine human exocrine pancreatic adenocarcinomas were examined by serial sectioning and double- and triple-labeled immunohistochemical techniques with antibodies against chromogranin A, insulin, islet amyloid polypeptide, glucagon, somatostatin, pancreatic polypeptide, serotonin, pancreastatin, and neuron-specific enolase. The results were correlated with the stage of the disease, histologic characteristics of the tumors, and survival of the patients. Cells immunoreactive with most or all of the antibodies were found in all nine cases. Abnormal co-location of some hormones in the same cell and the lack of normal co-location of other hormones were found. Endocrine cells also were identified in the invasive regions of the cancer, including perineural spaces. Abnormality in the production and release of the peptide was indicated not only in the endocrine cells of exocrine cancer, but also in the islets near the cancer. Patients whose cancer contained many endocrine cells seemed to survive longer than those with tumors containing fewer endocrine cells. The overall data suggested that the observed abnormalities may contribute to the impaired glucose tolerance found in six of these patients.